Barriers in Functioning of Dairy Enterprise Managed by Rural Women - Kumar, Arun; Singh, Prakash; Sahu, R. P.; Singh, Khushbu (Indian Journal of Extension Education, 2014)
This study was undertaken in the year of 2011 in Faizabad district of Uttar Pradesh with 120 respondents (60 rural women  from SHG and 60 rural women from non-SHG of dairy enterprise). The main objective of this study was to find out the  barriers in functioning of dairy enterprise managed by rural women. Majority of the SHG rural women faced the barriers  as chances of dishonesty regarding handling of money, poor economic access of women to invest in dairy enterprise, lack  of training programme, improper supply and high cost of veterinary services and medicines, lack of proper marketing  channels. The majority of the non-SHG women faced hindrance of casteism hinders in proper SHG formation, improper  supply and high cost of veterinary services and medicines, lack of training programmes and lack of proper marketing  channels. Most of the independent variables viz., age, family size, occupation, mass media sources, overall extension  contact, farm power, agricultural implements etc. were found highly significant and positively correlated with degree of  women empowerment.
Keywords: Self Help Group (SHG); barriers; rural women; dairy enterprise; women empowerment